Nexus between Sources of Electricity Production and Environmental Degradation in Context of EKC Hypothesis: A Time Series Study for Pakistan - Haq, Ihtisham ul; Embergenov, Bakhitbay; Allayarov, Piratdin (International Journal of Energy Economics and Policy, 2022)
This time series study is carried out to determine effect of sources of electricity production on environmental degradation in Pakistan in context of environmental Kuznets curve (EKC) hypothesis. Moreover, this study also examines effect of rural and urban population on environmental degradation. This study considers carbon emissions from electricity and heat as a proxy for environmental degradation. Unit root tests are applied to determine level of integration of time series variables. Bounds test is applied to examine long run relationship among variables. This study finds that hydro, natural gas and nuclear sources of electricity production have negative significant effect on environmental degradation whereas electricity production from oil sources has positive and significant effect on environmental degradation. Electricity from coal has positive effect on environmental degradation but its effect is not significant. Results of the study confirms EKC hypothesis in Pakistan. Besides, results indicate that rural population and urban population is negatively and positively associated with environmental degradation respectively. This study suggests that energy policy has to be design in such manner that on one hand, it tackles energy crisis, on other hand, it leads to sustainable development in Pakistan.